Production potential and economic feasibility of sesame (Sesamum indicum) - based intercropping with legumes under rainfed conditions - KUMAR, ANIL; THAKUR, K S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during rainy season of 2002 and 2003 under rainfed conditions at Oilseeds Research Station, Kangra to find out the most appropriate sesame based intercropping system and their planting pattern for higher productivity and returns. The sesame yield decreased with soybean and blackgram intercropping in all planting pattern by 49.6-69.1 and 41.7-64.7 % respectively. Sole soybean gave the highest sesanle equivalent yield (0.715 tonnes/ha) and net returns (Rs 16 010), whereas sesanle sole the lowest yield (0.456 tonne/ha) and returns (Rs 8 792). Intercropping in sesanle with soybean and blackgran1 increased its productivity by 22.8-32.7% over the sole sesame cropping. Both the sesame and intercrops in the system were equally competitive when broadcast and 1:1 planting pattern, whereas paired row planting of intercrop dominated the sesame crop. Among intercropping systems sesame +blackgram (1:1) gave the maximum land equivalent ratio (1.17), sesame equivalent yield (0.605 tonne/ha) and net return (Rs 13 510).